Addition of copeptin improves diagnostic performance of point-of-care testing (POCT) for cardiac troponin T in early rule-out of myocardial infarction — A pilot study. (1st November 2015) - Vafaie, Mehrshad; Biener, Moritz; Mueller, Matthias; Abu Sharar, Haitham; Hartmann, Oliver; Hertel, Sabine; Katus, Hugo A.; Giannitsis, Evangelos
Abstract: Background: Point of care testing (POCT) assays for cardiac troponin (cTn) are hampered by lower analytical sensitivity and thus suboptimal rule-out of myocardial infarction (MI). We investigated, whether additional measurement of copeptin using an ultrasensitive assay improves diagnostic performance of POCT for cTn T compared to a high sensitivity troponin T (hsTnT) assay. Methods: 131 patients with suspected acute coronary syndrome were prospectively enrolled in our center 08/2010 to 11/2011. In blood samples obtained at presentation, ultrasensitive copeptin (Kryptor, BRAHMS) and two commercially available POCT assays, AQT90 Flex Radiometer (Radiometer) and Cobas h232 POC-System (Cobas), were tested. HsTnT (Cobas E411, Roche) at baseline and after 3 and 6 h in the central laboratory served as reference. Results: Copeptin improved rule-out of non-STEMI combined with all tested troponin assays. Addition of copeptin increased sensitivity of Cobas from 67.9% (95% CI: 0.506; 0.852) to 89.3% (95% CI: 0.778; 1.007) and Radiometer from 71.4% (95% CI: 0.547; 0.882) to 85.7% (95% CI: 0.728; 0.987), achieving the sensitivity of hsTnT alone at admission of 85.7% (95% CI: 0.728; 0.987). The area under the curve (AUC) of Radiometer (0.822) was numerically but insignificantly (p = 0.17) higher than AUC of Cobas (0.725). Addition of copeptin increased AUC of Radiometer to 0.826 (p = 0.96) and AUC of Cobas to 0.814 (p = 0.20). Conclusions: Additional use of ultrasensitive copeptin improves diagnostic performance of conventional sensitive POCT assays overcoming lower sensitivities at the cost of a drop of clinical specificity. When hsTn is temporarily unavailable, copeptin and POCT for cTn may allow initial evaluation at a comparable performance as hsTnT at admission. Highlights: Copeptin was measured in addition to POCT assays for troponin T and hsTnT. Diagnostic performance for rule-out of non-STEMI was improved in all assays. Higher sensitivity and NPV come at a cost of lower specificity. Copeptin and POCT for troponin T may allow initial evaluation at a comparable performance as hsTnT at admission.